Adoption of E-commerce Payment Systems by Commercial Banks in Kenya (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
E-commerce, which is combination of traditional commerce and Internet, has brought dramatic changes of the way business transactions are conducted prompting banks, as the intermediary financial instruments, to adopt and adapt electronic payment systems (EPS). These e-payment systems which include debit and credit cards, electronic fund transfer, mobile payments platforms and internet banking are already in use in Kenya market. Importantly to note is the fact that electornic payment instruments are not used with equal intensity even in developed countries due to various reasons. The research thus is focused on identifying key drivers for adoption of EPS in Kenya market by banks.The researcher identified major variables affecting adoption of EPS which included security status, perceived level of trust, infrastructure capability to handle the system, marginal cost reduction and perceived associated benefits. A descriptive census survey of all the 43 banks was then done through a structured questionnaire. With a id of technology acceptance model and DeLone & McLean Information System Success model, the data collected was empirically analysed and results presented.With different intensity, the findings of the study revealed that many banks in Kenya are implementing EPS platforms. The driving forces for the adoption are the factors identified in the conceptual framework of this study. Bank respondents successfully did the rating of these factors. Therefore, the study recommends for a concerted effort amongst EPS key players to streamline operations in their area of concern. They should establish policies and legal framework good for electronic transactions as well as building sound telecommunication infrastructure countrywide. Again, this study is just but a stepping-stone to a better analysis that will unlock the potential of e-payment systems. The researcher encourages both academicians and practitioners to critique the study findings.